Climate change impacts on meteorological, agricultural and hydrological droughts in China - Leng, Guoyong; Tang, Qiuhong; Rayburg, Scott (Global and planetary change, 2015)
Bias corrected daily climate projections from five global circulation models (GCMs) under the RCP8.5 emission scenarios were fed into a calibrated Variable Infiltration Capacity (VIC) hydrologic model to project future hydrological changes in China. The standardized precipitation index (SPI), standardized runoff index (SRI) and standardized soil moisture index (SSWI) were used to assess the climate change impact on droughts from meteorological, agricultural, and hydrologic perspectives. Changes in drought severity, duration, and frequency suggest that meteorological, hydrological and agricultural droughts will become more severe, prolonged, and frequent for 2020–2049 relative to 1971–2000, except for parts of northern and northeastern China. The frequency of long-term agricultural droughts (with duration larger than 4months) will increase more than that of short-term droughts (with duration less than 4months), while the opposite is projected for meteorological and hydrological droughts. In extreme cases, the most prolonged agricultural droughts increased from 6 to 26months whereas the most prolonged meteorological and hydrological droughts changed little. The most severe hydrological drought intensity was about 3 times the baseline in general whereas the most severe meteorological and agricultural drought intensities were about 2 times and 1.5 times the baseline respectively. For the prescribed local temperature increments up to 3°C, increase of agricultural drought occurrence is predicted whereas decreases or little changes of meteorological and hydrological drought occurrences are projected for most temperature increments. The largest increase of meteorological and hydrological drought durations and intensities occurred when temperature increased by 1°C whereas agricultural drought duration and intensity tend to increase consistently with temperature increments. Our results emphasize that specific measures should be taken by specific sectors in order to better mitigate future climate change associated with specific warming amounts. It is, however, important to keep in mind that our results may depend on the emission scenario, GCMs, impact model, time periods and drought indicators selected for analysis. •More severe, prolonged, and frequent droughts are projected in the future in China.•Climate warming would induce more extreme droughts than mean droughts.•Changes in meteorological, agricultural and hydrological droughts are different.•Agricultural drought tends to increase with climate warming from 0.5 to 3K.•1K warming causes the largest impact on meteorological and hydrological droughts.